A presentation of postcardiac injury syndrome after successful chronic total occlusion percutaneous coronary intervention using dissection re‐entry techniques - Elbaz‐Greener, Gabby (Clin Case Rep, 2017)
Retrograde dissection re‐entry can cause pericardial trauma of sufficient degree to lead to the development of an auto‐immune postpericardial injury syndrome. Clinical suspicion for this condition should be high in the event of fever, symptoms, pericardial/pleural effusion, and pleuritic chest pain following chronic total occlusion (CTO) Post cardiac injury syndromes (PCI).